The Jewish people in Christian preaching - Fasching, Darrell J., 1942- (New York : The Edwin Mellen Press, 1984)
Papers based on a symposium " New horizon or old dilemmas?: Judaism in Christian theology and preaching" held at the Temple Society of Concord and the Syracuse, N.Y., Oct. 15, 1979, co-sponsored by Hendricks Chapel and the B.G. Rudolph Lectures in Judaic studies of Syracuse University and the Syracuse Area Interreligious Council.
Includes bibliographies and index
Keywords: Judaism (Christian theology) -- Congresses; Preaching -- Congresses; Christianity and other religions -- Judaism -- Congresses; Judaism -- Relations -- Christianity -- Congresses